Congenital Ectropion Uveae with Glaucoma: A Case Report - Kumari, Rashmi (J Clin Diagn Res, 2017)
Congenital Ectropion Uveae (CEU) is a rare anomaly characterised by ectropion uveae, iris hypoplasia, iridotrabecular dysgenesis and glaucoma. Hyperplasia of the iris pigment epithelium and its apparent spread over the anterior surface of the iris is supposed to cause the classic ectropion uveae in CEU. Almost all patients develop open angle glaucoma due to angle dysgenesis, so they should be carefully examined periodically for its early detection. We hereby report a case of isolated unilateral CEU without any systemic association which is quite uncommon. Loss of vision went unnoticed while the facial asymmetry secondary to progressive enlargement of one eye became the presenting complain due to this rare unilateral affliction.